A novel Non-rodent animal model of hydrochloric acid-induced acute and chronic lung injury - Pavel A. Solopov; Ruben Manuel Luciano Colunga Biancatelli; Tierney Day; Christiana Dimitropoulou; John D. Catravas (Respiratory Research)
Abstract Hydrochloric acid is one of the most prevalent and hazardous chemicals. Accidental spills occur in industrial plants or during transportation. Exposure to HCl can induce severe health impairment, including acute and chronic pulmonary diseases. We have previously described the molecular, structural, and functional aspects of the development of chronic lung injury and pulmonary fibrosis caused by intratracheal instillation of HCl in mice. Although mouse models of human disease have many advantages, rodents are evolutionary far from human and exhibit significant anatomical and physiological differences. Genetic and anatomic similarities between rabbits and humans are significantly higher. Rabbit models of HCl-induced lung injury have been used sparsely to evaluate acute lung injury. In this study, for the first time, we utilized rabbits as a model of HCl-induced pulmonary fibrosis and chronic lung injury. We present molecular, histological, and functional evidence that demonstrate the utility of using this model for studying new pharmaceutics against pulmonary fibrosis.